2018
DOI: 10.1111/fcre.12378
|View full text |Cite
|
Sign up to set email alerts
|

The Benefits, Drawbacks, and Safety Considerations in Digital Parent–Child Relationships: An Exploratory Survey of the Views of Legal and Mental Health Professionals in Family Law

Abstract: The surge in information and communication technologies (ICT) has provided alternative opportunities for maintaining parent–child contact postseparation. This article highlights findings from a survey study of 103 legal and mental health professionals who shared their views on the benefits and drawbacks of the use of ICT in parent–child contact postseparation. Results revealed a significant increase in the use of ICT as an enhancement tool for maintaining parent–child relationship in today's modern families. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(27 citation statements)
references
References 13 publications
0
21
0
6
Order By: Relevance
“…Hostility or conflict between the adults can also result in a feeling of divided loyalty for the foster child, leading to a belief that she/he must choose between the birth parent and foster parent. These kinds of challenges are similar to the difficulties that exist for divorced parents who are in conflict (Saini & Polak, 2018) and may be more likely to occur in kinship foster placements when there is a history of intrafamilial conflict. Parents may try to manipulate the child or withhold information which essentially undermines the purpose of the video exchange (Ganong et al, 2012).…”
Section: Relationship Dynamics and Challenges With Virtual Visitationsmentioning
confidence: 86%
See 1 more Smart Citation
“…Hostility or conflict between the adults can also result in a feeling of divided loyalty for the foster child, leading to a belief that she/he must choose between the birth parent and foster parent. These kinds of challenges are similar to the difficulties that exist for divorced parents who are in conflict (Saini & Polak, 2018) and may be more likely to occur in kinship foster placements when there is a history of intrafamilial conflict. Parents may try to manipulate the child or withhold information which essentially undermines the purpose of the video exchange (Ganong et al, 2012).…”
Section: Relationship Dynamics and Challenges With Virtual Visitationsmentioning
confidence: 86%
“…Separation from parents can be extremely stressful for children, increasing their risk for adjustment difficulties (Kobak et al, 2016). In order to bridge the gap created by separation between children and their loved ones, virtual contact has been utilized in a number of areas of family life including families with incarcerated parents (McLeod & Bonsu, 2018;Phillips, 2012;Skora & Poehlmann-Tynan, 2020), military families (Mathew-Juarez et al, 2013;Mogil et al, 2015), families with divorced parents (LaMarca, 2012;Saini & Polak, 2018;Saini et al, 2013), extended family members (e.g., grandparents) (McClure et al, 2018) and child welfare families (Iyer et al, 2020;Neil et al, 2020;Quinn et al, 2015). Research in these areas has found that children can benefit significantly in terms of knowledge development, emotional well-being and relationship maintenance from virtual communication with parents and others from whom they are separated.…”
Section: Virtual Parent-child Communicationmentioning
confidence: 99%
“…Furthermore, it is crucial to consider the needs, rights, and perceptions of children and adolescents when planning digital contact (Saini & Polak, 2018), as well as the age and maturity of the child and their preferences. According to Saini et al (2013), virtual contact forms could be integrated at any stage to become longer and more complex as the children grow.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies reported on the perspective of both birth parents and children (Wolman & Pomerance, 2012;Yarosh et al, 2009). The remaining studies explored only the perspective of professionals (Quinn, 2015;Saini & Polak, 2018) or parents (Castelain-Meunier & Libbrecht, 1997;Dworkin, 2016;Maupas, 2019). Finally, four studies combined qualitative and quantitative methods, one study used a quantitative design, and six used a qualitative design.…”
Section: Description Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation